Expression of a Novel HIV-1 Gag-Pol-Env-Nef-Rev Multi-Epitope Construct in Escherichia coli - Elahe Akbari; Soheila Ajdari; Esmat Mirabzadeh Ardakani; Elnaz Agi; Vahid Khalaj; Azam Bolhassani (Journal of Medical Microbiology and Infectious Diseases)
Introduction: Recombinant subunit vaccines have been explored against various human pathogens, however, developing an effective therapeutic toward human immunodeficiency virus (HIV) infection has been challenging. So far, several recombinant HIV-1 antigens have been produced and examined for activation of desired immune responses. This study aimed to express an HIV-1 multiepitope protein as an antigen candidate to develop a vaccine.  Methods: In this study, the codon-optimized encoding sequence of the designed multi-epitope construct (Gag-Pol-Env-Nef-Rev) was synthesized and subcloned into the pET-24a (+) expression vector. Then, expression of the target antigen was evaluated in E. coli BL21 (DE3) and Rosetta strains under different conditions (temperature, optical density/ OD600, isopropyl β-D-1-thiogalactopyranoside (IPTG) concentration, and time). Finally, the expression of the Gag-Pol-Env-Nef-Rev multi-epitope protein was confirmed using SDS-PAGE and western blot analysis.  Results: The highly conserved and immunodominant T-cell epitopes of HIV-1 Gag, Pol, Env, Nef, and Rev proteins were used to prepare a novel Gag-Pol-Env-Nef-Rev multi-epitope construct. The gag-pol-env-nef-rev gene was successfully sub-cloned in pET-24a (+) vector and subsequently expressed in BL21 (DE3) E. coli strain under optimized conditions (1 mM IPTG, 16 h post-induction, OD 600= 0.6, and 37ºC). A clear band of ~ 35 kDa was detected by western blotting using an anti-His antibody, indicating the successful expression of our target multi-epitope protein. Conclusion: Expression of the recombinant HIV-1 multi-epitope protein was optimized in a bacterial system. The expressed protein will be purified to use as a multi-epitope protein vaccine candidate in the future.